Violations of the Prudential Principle and Fraudulent Practices in Indonesia’s Capital Market: A Case Analysis of OJK Sanctions Against Listed Firms - Dewa Putu Yohanes Agata L. Sandopart; Lie Adek; Dewa Ayu Indiana Ida Loemongga Sandopart; Erma Wijayanti (Journal of Economics and Management, 2025)
This research investigates how breaches of the prudential principle contribute to fraud within Indonesia’s capital market, focusing on listed entities penalized by the Financial Services Authority (OJK). Utilizing a qualitative multiple-case study approach, the analysis centers on four prominent cases: PT Repower Asia Indonesia Tbk (REAL), PT Multi Makmur Lemindo Tbk (PIPA), PT Bliss Properti Indonesia Tbk (POSA), and PT Mirae Asset Sekuritas Indonesia. Secondary data were gathered from OJK official statements, sanction rulings, national media reports, and legal documents spanning 2022–2025. Through pattern-matching and cross-case synthesis, three recurring violation patterns emerged: inadequate customer due diligence by underwriters, submission of inaccurate information during share subscription and allocation, and lapses in directors’ internal oversight. Fraudulent schemes primarily involved masking true beneficial ownership via nominee structures and offshore vehicles, alongside the fictitious recognition of assets financed by IPO proceeds. OJK’s enforcement strategy demonstrates a tiered, proportionate approach that extends to market intermediaries and, in select instances, crosses national borders. A notable systemic flaw identified is an enforcement delay of up to two years, which may weaken deterrence. The study validates the applicability of the fraud pentagon framework in emerging markets and offers actionable recommendations for enhancing risk-oriented supervision.